2023
DOI: 10.3389/fevo.2023.1158887
|View full text |Cite
|
Sign up to set email alerts
|

Migrant orangutan males use social learning to adapt to new habitat after dispersal

Julia Mörchen,
Frances Luhn,
Olivia Wassmer
et al.

Abstract: Dispersal has been suggested to be challenging, especially for species that heavily rely on social learning for knowledge acquisition. One of the obstacles that migrants face is learning how to cope with an unfamiliar, new habitat, which may involve learning from resident individuals. So far, only very few studies have looked at social learning in migrants after dispersal. Here we examine how migrant male orangutans use a behavior called “peering” (an indicator of observational social learning), to learn from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 110 publications
(151 reference statements)
0
5
0
Order By: Relevance
“…Second, unflanged male sociality may also serve to establish longterm relationships with females , which may eventually lead to higher reproductive success. Third, sociality of recently dispersed unflanged males may not only serve reproductive strategies but also acquisition of local ecological skills (Mörchen et al, 2023). The observed decrease in female associates with years since first observation in the crosssectional dataset may provide evidence for the latter two explanations of unflanged male sociality.…”
Section: Association Patterns With Femalesmentioning
confidence: 88%
“…Second, unflanged male sociality may also serve to establish longterm relationships with females , which may eventually lead to higher reproductive success. Third, sociality of recently dispersed unflanged males may not only serve reproductive strategies but also acquisition of local ecological skills (Mörchen et al, 2023). The observed decrease in female associates with years since first observation in the crosssectional dataset may provide evidence for the latter two explanations of unflanged male sociality.…”
Section: Association Patterns With Femalesmentioning
confidence: 88%
“…As Fibraurea tinctoria has potent analgesic effects, individuals may feel an immediate pain release, causing them to repeat the behavior several times and subsequently apply solid plant matter possibly to also cover the wound as a protection against flies (as the case reported here suggests). Immature orangutans rely on observational social learning for the acquisition of their skill repertoires 64 and recent evidence suggests that social learning continues into adulthood 65 . Therefore, given that it occurs frequent enough and in social contexts, wound treatment with Fibraurea tinctoria may also spread socially from individual to individual.…”
Section: Discussionmentioning
confidence: 99%
“…The variety of animal species examined as well as evidence of performances with basic cultural features have markedly increased. Ethological research has produced studies on the pace of animal innovations, as found in seasonal changes in songs of humpback whales (Schulze et al, 2022 ), on cultural transmission in the manufacture of tools, as in New Caledonian crows (Hunt & Gray, 2003 ), and on the adoption of new behavioural elements from resident individuals when they must adapt to new habitats after dispersal, as in male orangutans (Mörchen et al, 2023 ). The current state of the field suggests that there is a variety of basic cultural performances in a wide array of animal orders from invertebrates to birds and mammals (Whiten, 2021 ) and that the number of (unspecified) cases of ‘culture’ is underestimated (Schuppli & Van Schaik, 2019 ).…”
Section: Methods: Models Experiments and Field Studiesmentioning
confidence: 99%